Concurrent activation potentiation improves lower-limb maximal strength but not dynamic balance control in rugby players - Rizzato, Alex; Dalla Costa, Vittorio G.; Bozzato, Matteo; Paoli, Antonio; Marcolin, Giuseppe (Frontiers in Bioengineering and Biotechnology, 2024)
Concurrent activation potentiation (CAP) increases athletic performance by activating muscles not involved in the performed activity. Among the CAP strategies, jaw clenching is the most practical to implement in sports contexts. Muscle strength and balance control are essential among rugby players to cope tackles. Besides combat sports, mouthguard has become mandatory also in rugby. Therefore, this study aimed to understand whether mouthguard jaw-clenching could improve rugby players' dynamic balance and quadriceps isometric strength. Thirteen rugby players were tested under maximal-bite (MB) and no-bite (NB) conditions. During standing balance tests, an electro-actuated platform with a force plate screwed on it allowed for the perturbation of the support base of the rugby players. A verbal signal warned the subject that the perturbation was coming, mentally recalling an in-field expected collision. In the first 2.5s window after the perturbation, the center-of-pressure (CoP) displacement and mean velocity were measured. The first peak, the maximal oscillations, and the standard deviation of the anterior-posterior CoP trajectory were calculated within the same time window. In the isometric leg-extension test, a custom-built chair instrumented with a uni-axial load cell allowed to collect the maximal strength and rate of force development (RFD). Mouthguard jawclenching did not affect CoP-related parameters but increased maximal strength (p<0.05) and RFD (0-50ms: p< 0.01; 50-100ms: p< 0.001; 100-150ms: p< 0.05) in the isometric leg-extension test.Mouthguard jaw-clenching alone could be useful to increase lower-limb maximal isometric strength and RFD but did not improve dynamic balance performance in a sport-oriented postural balance test.